2022
DOI: 10.3390/jcm11030824
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Inhibitors and the Gut

Abstract: Checkpoint inhibitors have revolutionized treatments in modern oncology, including many conditions previously relegated to palliative therapies only. However, emerging recognition of checkpoint inhibitor-related adverse events has complicated the status of checkpoint inhibitor-related therapies. This review article discusses gastrointestinal adverse events as a result of checkpoint inhibitor therapy, as well as limitations of current guidelines, thus providing recommendations for guideline revision and future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…As described above, our patient suffered from severe complications during the different medical treatments (catheter-related infections, sepsis by a bacterial translocation) and no further benefit was expected from immunosuppressive therapy. In contrast, the poor general nutritional status, the long-lasting use of corticosteroids, and the resection of the long bowel segment hampered our decision for earlier surgery [26] .…”
Section: Discussionmentioning
confidence: 99%
“…As described above, our patient suffered from severe complications during the different medical treatments (catheter-related infections, sepsis by a bacterial translocation) and no further benefit was expected from immunosuppressive therapy. In contrast, the poor general nutritional status, the long-lasting use of corticosteroids, and the resection of the long bowel segment hampered our decision for earlier surgery [26] .…”
Section: Discussionmentioning
confidence: 99%
“…The reason behind this exclusion was not mentioned by the authors; however, we believe that it is of particular value. Previous studies showed that IMC could occur at any time following immunotherapy complicating the management of cancer patients[ 4 ]. The reported incidence ranges from 3 to 21% for mild and 5 to 17% for severe cases[ 5 ].…”
Section: To the Editormentioning
confidence: 99%
“…Up to two-thirds of all patients undergoing ICI therapy will have immune-related adverse events (irAEs). Along with endocrinologic and dermatologic irAEs, gastrointestinal symptoms including immune checkpoint inhibitor colitis (ICIC) are among the most common irAEs [1]. This review summarizes the most valuable and currently available information about the mechanism, diagnosis, and management of ICIC.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is difficult to predict who will develop ICICs, risk factors have been identified as preexisting autoimmune disease, previous irAEs, chronic use of anti-inflammatory agents, and certain compositions of the gut microbiome. However, in contrast to other known autoimmune diseases such as systemic lupus erythematosus or rheumatoid arthritis, inflammatory bowel disease (IBD) is not known to be a risk factor for irAEs [1]. One study found an association between increased leukocytes and absolute number of neutrophils at the start of immunotherapy with the occurrence of irAEs.…”
Section: Introductionmentioning
confidence: 99%